Rozvoj cestovního ruchu v Pardubickém kraji - Šimková, Alena (Univerzita Pardubice, 2006)
Cílem této práce je provést analýzu jednotlivých druhů cestovního ruchu v Pardubickém kraji, se zaměřením na kvalitu poskytovaných služeb a nalézt nové příležitosti pro jeho rozvoj. Zvláštní důraz je věnován kulturnímu cestovnímu ruchu, především aktivitám a managementu Východočeského divadla. Při hledání nových možností je pro rozvoj cestovního ruchu využita SWOT analýza, tabulky a grafy.

The goal of the work is to analyze various tourism arts in the Pardubice region, aimed at quality of the services provided, and to finad new opportunities for the tourism development. Particular attention is given to the cultural tourism segment, especially activities and management of the East Bohemian Theatre. The SWOT analysis, tables and charts are used while looking for the new opportunities for the tourism development mentioned above.
Tourism development in the Pardubice region
Keywords: Cestovní ruch; Pardubice; Rozvoj